Market Value dan Risiko Saham terhadap Holding Period dalam Perspektif Investasi - Siti Diva Syarifah Lukman (Amsir Management Journal, 2023)
This study aims to determine the effect of Market Value and Stock Risk on Holding Period in The Perspective of Investing in Cigarette Companies listed on The Indonesia Stock Exchange (IDX). The analttical method used in this study is multiple linear regression analysis, classical assumption test, coefficient of determination and hypothesis testing using statistical t test with SPSS version 26.0. The observation period carried out is 2019-2021. The result of this study prove that Market Value has a positive and significant effect on Holding Period and Stock Risk has a negative and insignificant effect on Holding Period in Cigarette Companies listed on IDX with an observation period of 2019-2021.